2011
DOI: 10.1002/chem.201102310
|View full text |Cite
|
Sign up to set email alerts
|

Pyridine‐Based Lanthanide Complexes Combining MRI and NIR Luminescence Activities

Abstract: A series of novel triazole derivative pyridine-based polyamino-polycarboxylate ligands has been synthesized for lanthanide complexation. This versatile platform of chelating agents combines advantageous properties for both magnetic resonance (MR) and optical imaging applications of the corresponding Gd(3+) and near-infrared luminescent lanthanide complexes. The thermodynamic stability constants of the Ln(3+) complexes, as assessed by pH potentiometric measurements, are in the range log K(LnL)=17-19, with a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
87
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 96 publications
(96 citation statements)
references
References 69 publications
9
87
0
Order By: Relevance
“…The apparent maxima of the spectrum of both complexes is at approximately 30800 cm -1 (325 nm), which is consistent with the singlet-state energies of other pyridine-containing complexes. [29] The addition of Zn [30] For instance, it has been shown that the nature and polarizability of the group occupying a position on or close to the principal axis of the complex affects the relative intensity of the 5 D 0 Ǟ 7 F 2 transition. [31] The more polarizable the axial donor atom is, the greater the relative The hydration states of the EuL1 and EuL2 complexes were studied by comparison of their luminescence lifetimes in H 2 O and D 2 O.…”
Section: Absorption and Emission Electronic Spectroscopymentioning
confidence: 99%
“…The apparent maxima of the spectrum of both complexes is at approximately 30800 cm -1 (325 nm), which is consistent with the singlet-state energies of other pyridine-containing complexes. [29] The addition of Zn [30] For instance, it has been shown that the nature and polarizability of the group occupying a position on or close to the principal axis of the complex affects the relative intensity of the 5 D 0 Ǟ 7 F 2 transition. [31] The more polarizable the axial donor atom is, the greater the relative The hydration states of the EuL1 and EuL2 complexes were studied by comparison of their luminescence lifetimes in H 2 O and D 2 O.…”
Section: Absorption and Emission Electronic Spectroscopymentioning
confidence: 99%
“…In addition, accommodating different metal ions within the same molecule can be exploited, fore xample, in magnetic [7] and/or opticald evices [8] and in multimodala gents for biomedical imaging, [9,10] but their controlled preparation remains challenging, especially in the case of 4f heteronuclear systems. [11, 12] Recently,s everalt etranuclear tetrahedral complexes built with lanthanides have been investigated.…”
mentioning
confidence: 99%
“…These include, among others, hydroxypyridinonate [39][40][41][42] , AZTA 43 , and DTTA derivatives 44 as well as pyridine-based amino carboxylate ligands. 45 The Gd-H distance, r GdH , which enters at the inverse sixth power into the expression of inner-sphere relaxivity, is a difficult parameter to obtain experimentally. It is generally estimated on the basis of Gd-coordinated water oxygen distances, determined by solid-state x-ray analysis.…”
Section: Hydration Number and Gd-h Distancementioning
confidence: 99%